Karakteristik Kimia dan Organoleptik Virgin Coconut Oil (VCO) dengan Penambahan Bubuk Daun Mint (Mentha piperita L.) - Siski S. Kandong; Lucia C. Mandey; Lana E. Lalujan; Jenny E. A. Kandou; Riel J. J. Umboh; Teltje Koapaha (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
This study aimed to determine the effect of adding mint leaf powder (Mentha piperita L.) at different concentrations (0%, 1.25%, 1.75%, and 2.25%) on the chemical and organoleptic characteristics of Virgin Coconut Oil (VCO). A Completely Randomized Design (CRD) with four treatments and three replications was used. Parameters tested included moisture content, free fatty acids (FFA), peroxide value, viscosity, and organoleptic attributes (color, aroma, taste) evaluated by 25 semi-trained panelists. Results showed that the addition of mint leaf powder significantly affected moisture content, peroxide value, and FFA. Moisture content (0.11-0.14%) and FFA (0.15-0.19%) met the SNI 7381:2008 standards, while the peroxide value (4.31-6.58 mg eq/kg) exceeded the maximum limit. Organoleptic tests indicated that the control treatment (P0) was most preferred by panelists compared to treatments with mint powder.